Plasmonic absorption enhancement in graphene circular and elliptical disk arrays. (18th January 2019) - Lin, Hang; Ye, Xin; Chen, Xifang; Zhou, Zigang; Yi, Zao; Niu, Gao; Yi, Yougen; Hua, Yanting; Hua, Jiangjin; Xiao, Shuyuan
Abstract: In this paper, a periodical array composed of patterned circular and elliptical disk graphene resonators on a silicon substrate spaced by a silicon dioxide dielectric layer is presented. Our research shows that the graphene arrays exhibit three absorption peaks of 16% at 26 μ m, 30% at 31 μ m and 34% at 45 μ m. The absorption performance of our structure can be improved by changing the structural parameters of the graphene layer (we studied the different structural parts of the model, the size and proportion of their values respectively), dielectric multiplier and Fermi energy level. According to our conception, the proposed structure can be used in the far infrared spectrum detector, filter and sensor.